Public Policies and the Bridge between Academia and Society: Lessons from the University Extension of the Department of Political Science (University of the Republic) - Martinez Rodríguez, Rodrigo (Journal Studies of Public Policy, 2024)
This article examines the interaction between academia and society in the field of public policies, based on the university extension experience of the Department of Political Science at the University of the Republic. Through a documentary analysis of institutional agreements and contributions to public debate in the press between 2011 and 2022, a predominance of collaborations with government entities is identified. These collaborations show significant variations following the 2020 change in government, highlighting a reliance on the demand for expert knowledge and questioning the relationship between science and politics. Additionally, challenges are noted in expanding the discipline to include departmental and local actors. Contributions to public debate focus on relevant contextual events and are characterized by objective assessments. In conclusion, the article emphasizes the need to strengthen connections with local actors to take on a more active role in the public policy-making process.